Homotopy Analysis Method of Internet Congestion Control Model - Yuliang Liu; Jinshu Lu; Hua Zhang; Lin Li (2010 International Conference on Communications and Mobile Computing, 2010)
Recently time-delayed dual model has attracted great attention in studying Internet congestion control. Stability analysis of time-delayed dual model is an important task, where how to determine its solution is the first step. Usually perturbation method can be used to seek the solution of the model, however, its effectiveness depends on a small parameter and it will be invalid when such a parameter doesn't exist. In this paper, we use a hyper-perturbation method called homotopy analysis method (HAM) to determine the solution, and its simplification and feasibility are proved by numerical simulations.